Design, Implementation, and Evaluation of a Location-Based System for Investigating the Parameters of Place Meaning for Visually Impaired Users - Rizopoulos, Charalampos; Lambrinos, Lambros; Gazi, Angeliki (My University, 2014)
This paper outlines the design, implementation, and evaluation methodology of a location-aware application intended as an aid to blind users who navigate urban spaces. The application is used in the context of a soundwalk whose purpose is to enable these users to indicate their level of emotional involvement with particular sounds emanating from specific areas of the city and provide a backdrop to the users' generation of place meaning based largely on auditory cues.
Keywords: Accessibility; Affective interaction; Location awareness; Place meaning; Soundscape